Epididymal sperm reserve in the indigenous pigs (Sus vittatus) of Assam - GOSWAMI, B K; DEKA, B C; BISWAS, R K (The Indian Journal of Animal Reproduction, 2023)
Twenty-seven indigenous pigs of Assam 4 to 12 months of age were used to study the sperm reserve inthe caput, corpus and cauda epididymis. The epididymis after castration was separated from the testes and dividedinto caput, corpus and cauda regions. The spermatozoa from each region of the epididymis was obtained byhomogenizing and filtering the homogenate. The sperm concentration in the filtrate was determined by directhaemocytometer method. The distribution of sperm (x 109) in caput, corpus and cauda was 1.02 ± 0.08 ( 17 .20% ),0.71± 0.05 (11.97%) and 4.19 ±0.21 (70.66%), respectively at 4 months of age which increased to 5.63 ± 0.20(17.09%), 3.37± 0.03 (10.23%) and 23.95± 0.6] (72.69%), respectively at 12 months of age. The epididymalsperm reserve increased significantly (P
Keywords: Indigenous pig; age; caput; corpus and cauda epididymis; sperm reserve; testis